1998
DOI: 10.1093/jmedent/35.6.1044
|View full text |Cite
|
Sign up to set email alerts
|

Infestation of the Southern Alligator Lizard (Squamata: Anguidae) by Ixodes pacificus (Acari: Ixodidae) and its Susceptibility to Borrelia burgdorferi

Abstract: To investigate the reservoir potential of the southern alligator lizard, Elgaria multicarinata (Blainville), for the Lyme disease spirochete, Borrelia burgdorferi Johnson, Schmid, Hyde, Steigerwalt & Brenner, 14 lizards were collected from 1 county on each side of the northern Central Valley of California. Seven animals were collected from a Placer County site (Drivers Flat) and a Yolo County site (Cache Creek) where B. burgdorferi had been isolated previously from Ixodes pacificus Cooley & Kohls. Overall, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 0 publications
0
37
0
3
Order By: Relevance
“…The western fence lizard (Sceloporus occidentalis) is an important host of subadult I. pacificus, but this species is reservoirincompetent (Lane and Loye, 1989;Lane, 1990;Lane and Quistad, 1998;Eisen et al, 2001). The diversion of subadult blood meals to certain species of lizards contributes to lower enzootic transmission of B. burgdorferi in the western than in the northeastern US (Lane and Quistad, 1998;Wright et al, 1998).…”
Section: Density Of Ticksmentioning
confidence: 99%
“…The western fence lizard (Sceloporus occidentalis) is an important host of subadult I. pacificus, but this species is reservoirincompetent (Lane and Loye, 1989;Lane, 1990;Lane and Quistad, 1998;Eisen et al, 2001). The diversion of subadult blood meals to certain species of lizards contributes to lower enzootic transmission of B. burgdorferi in the western than in the northeastern US (Lane and Quistad, 1998;Wright et al, 1998).…”
Section: Density Of Ticksmentioning
confidence: 99%
“…Previous work has demonstrated that Borrelia genospecies (specifically B. burgdorferi sensu stricto, B. afzelii, B. garinii, B. japonica, and B. valaisiana) vary in their sensitivities to different host-serum complement including deer, rodent, avian, and reptilian sera (Kurtenbach et al, 1998;Kuo et al, 2000;Nelson et al, 2000). Borrelia bissettii belongs to the B. burgdorferi sensu lato complex and has been found throughout North America and in Europe (Picken et al, 1996;Postic et al, 1998;Wright et al, 1998;R.N. Picken and M.M.…”
mentioning
confidence: 99%
“…In case of the southern alligator lizard attempts to isolate spirochetes from lizard blood were unsuccessful (Wright et al 1998). These data suggested that this species is not a competent reservoir for B. burgdorferi s.l.…”
Section: Discussionmentioning
confidence: 99%
“…There are few papers dealing with infestation of various reptile species by ticks. Research has been focused mainly on temporal trends and environmental correlates of prevalence and abundance of ticks infesting western fence lizards (Sceloporus occidentalis) (TalleklintEisen and Eisen 1999, Eisen et al 2001, Casher et al 2002, five-lined skink (Eumeces fasciatus), broad-headed skink (Eumeces laticeps), eastern fence lizard (Sceloporus undulatus) (Kollars et al 1999) and southern alligator lizard (Elgaria multicarinata) (Wright et al 1998) in America, and sand lizard (Lacerta agilis) (Matuschka et al 1991) and Lacerta bilineata (Scali et al 2001) in Europe. Opinions about the competence of reptiles as a reservoir for tick-borne pathogens differ.…”
Section: Introductionmentioning
confidence: 99%